Quantification and Verification of Swingarm Structural characteristics through Numerical Simulation and Photogrammetry - Gregor, Lukas; Zouhar, Jan; Kupcak, Radim (Manufacturing Technology Journal, 2024)
Composite materials have consistently been applied in areas where a combination of properties such as strength, stiffness, and low weight is crucial. Motorcycle construction is no exception, as these parameters significantly impact riding characteristics, safety, and overall performance. This article focuses on quantifying the torsional and vertical stiffness of a single-sided swingarm made of carbon fiber reinforced polymer (CFRP) using finite element analysis (FEA) and verifying these results through experimental measurements. To enhance the accuracy of the simulations, which involve complex geometries and anisotropic materials, the material properties of selected fabrics used in the prototype production were measured. Specific fixtures were designed for the experimental measurements, enabling the application of torsional moments and vertical forces. Deformation under these loads was evaluated using the TRITOP photogrammetric system, which tracks deformations by monitoring the displacement of reference points under static load conditions and comparing them to a reference, unloaded state. Based on the acquired data, the overall stiffness values and their distribution along the length of the swingarm were calculated. The results showed a significant difference between simulation and reality. For the overall torsional stiffness, the simulated value was 249 N.m/°, while the measured was 270 N.m/°, showing a discrepancy of 7.7%. The vertical stiffness value from simulation was 414 N/mm, compared to 411 N/mm from experimental measurements, with a minimal difference of -0.7%. The stiffness distribution along the length of the swingarm exhibited a correlation, but with notable variation in certain areas. This confirms that accurately simulating CFRP parts with complex geometries is highly challenging, partly due to the sensitivity of the manufacturing process. Therefore, verification through experimental measurement is considered good practice.
Keywords: Swingarm; Torsional stiffness; CFRP; Photogrammetry; Stiffness distribution